Implementation of the Zakat Village Index to Support a Zakat Community Development Program in Bedono Village, Demak District - Farikhatusholikhah .; Tanti Novianti (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
BAZNAS is the organization that manages zakat on a national level, working toward alleviating poverty in Indonesia through its Zakat Community Development (ZCD) program. The ZCD program focuses on community-based development through the empowerment of the mustahik community living in rural areas. This study aims to measure the level of welfare and determine the eligibility of Bedono Village, Demak District to receive assistance in the form of zakat funds through the ZCD program. This research employed a survey method using interviews and focus group discussion, combined with a questionnaire. The analytical tool used in this analysis is the Multi-Stage Weighted Index. This research reveals the condition of Bedono Village to be “fairly good,” with an index score of 0.49. This means that Bedono Village can be considered for eligibility to receive help in the form of zakat.